Keberhasilan Praktik Bermain pada Pembelajaran Penjas di SD Negeri 105287 dalam Menciptakan Pembelajaran yang Aktif dan Kreatif - Rani, Cahaya; Pratiwi, Diana Eka; Hidayat, Yufa Ainun; Humaira, Siti Syalwa; Suyono, Suyono (LPPPI Publishing, 2025)
Play practice is one of the effective strategies in learning Physical Education (Penjas) at the elementary school level. This research aims to evaluate the success of play practices in creating an active, creative and enjoyable learning atmosphere at SD Negeri 105287. The research was conducted using a qualitative approach through interviews with students, Physical Education teachers and the principal Hj. Dewi Susanti, S.Pd., M.Sc., as well as direct observation of student activities during learning. The research results show that playing practice can significantly increase students' courage, activeness and creativity. Study teachers have succeeded in integrating play elements into learning activities, thus motivating students to participate actively. This research underscores the importance of play practices in creating interactive learning environments.